Development of GeoGebra-Based Learning Media for Flat Field Analytical Geometry Courses for Students of the Mathematics Education Department - Dewi Asmarani; Umy Zahroh; Santi Dewanti (Journal of Research on Mathematics Instruction (JRMI), 2022)
All aspects of life, including the education system, have undergone many changes due to the Covid-19 pandemic. We need media that can facilitate and attract students to carry out learning activities. This study aims to develop GeoGebra-based mathematics learning media. The method used in this research is Research and Development (R&D) with the ADDIE model (Analysis, Design, Develop, Implement, and Evaluate). The research was carried out at UIN Sayyid Ali Rahmatullah Mathematics Study Program in semester 3. The research subjects for the small-scale field test were class A, which had 32 students; for the large-scale field test, there were 132 students in Mathematics Education 3rd Semester. The results of research on the development of GeoGebra-based learning media in the Flat Analytical Geometry course for students majoring in Mathematics Education at UIN Sayyid Ali Rahmatullah Tulungagung were declared valid, practical and effective. The future hope for developing similar media is to expand the scope of the material discussed because the media developed is limited to flat analytic geometry operations.